2020
DOI: 10.1177/0309324720923218
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on fracture characteristics of notched granite beams under cyclic loading and unloading

Abstract: In underground engineering, such as mining engineering and deep tunnel engineering, the rock is often loaded and unloaded repeatedly. The strength of rock under cyclic load is lower than that under static load. To obtain the fracture response of the rock, the three-point bending tests of notched granite beams under cyclic loading and unloading were carried out with Electro-hydraulic Servo Material Test System. The acoustic emission technology was adopted to monitor the acoustic emission events of sample in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Zhang et al (2015) used the method of combining AE and DIC to study the deformation and failure process of sandstone rock beam specimens under three-point bending load, and reached similar conclusions with Wang et al (2018). Both Li et al (2020) and Du et al (2020) analyzed the distribution of RA-AF obtained in the AE test, and studied the classification of cracks in the process of rock beams fracture.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Zhang et al (2015) used the method of combining AE and DIC to study the deformation and failure process of sandstone rock beam specimens under three-point bending load, and reached similar conclusions with Wang et al (2018). Both Li et al (2020) and Du et al (2020) analyzed the distribution of RA-AF obtained in the AE test, and studied the classification of cracks in the process of rock beams fracture.…”
Section: Introductionmentioning
confidence: 74%
“…This shows that the AE energy of low-strength rock beams is mainly concentrated in the low-energy range, and high-strength rock beams also have AE counts in the high-energy range. The RA value (RA= rise-time/ peak amplitude) changes with AF (AF=ring down counts/ duration) in the AE signals and carries important information, which can be used to distinguish different crack modes (Li et al 2020). Higher AF and lower RA represent tensile failure, and lower AF and higher RA represent shear failure.…”
Section: Influence Of Rock Lithologymentioning
confidence: 99%
“…Currently, many scholars primarily use indoor experiments to study the mechanical properties of rocks under cyclic loading and unloading. Li, X. et al [6] conducted cyclic loading and unloading three-point bending tests on granite notched beams to analyze the fracture characteristics of granite. The study found that the fracture toughness of granite under cyclic loading and unloading is lower than that under static loading.…”
Section: Introductionmentioning
confidence: 99%